A tale of three cities; benchmarking Clinical Ethics Services (CES) in three continents. (24th May 2012) - Larcher, V
Abstract : Aims: Cinical Ethics Services (CESs) provide advice, support and training for those facing ethical dilemmas in clinical practice. Whilst benchmarks for CESs in adult medicine exist, those for paediatrics are less well reviewed and no national comparisons have been made. We therefore examined CESs at 3 specialist children's hospitals in US, UK. Australia (Aus) to determine how they conformed to established benchmarks or set standards for practice. Methods: Review of terms of reference (ToR), operating procedures, activity data: semi-structured interview with service leads: comparison with published benchmarks/standards Results: Demographics Hospitals were comparable in size, complexity and activity; CESs had evolved from clinical ethics committees that remained integral to service. More ethicist [and administrator] time was funded in the US than in Aus or UK (3WTE vs i.2 and 0.3 respectively) Functions: All ToR reflected national adult standards and provided:- acute case consultations, reflective case analysis, education of professionals, input to institutional policy-making. Case consultations All CESs had procedural rules for making referrals and convening, recording and reporting discussions. Normal practice involved small CES member-led group discussions. In the US consultations were often 2-staged with families and professionals attending separately; this was not standard in UK or usual in Aus. Activity profiles were similar for numbers of cases (16->40 pa) and issues raised (end-of life decision-making, treatment requests/refusals, resource-usage). Education and training: Additional to that delivered incase discussions was more formally organised in the US and Aus, with funded academic support. Many CES members had publications in clinical ethics even in the absence of formal research projects. Policy development all CESs had contributed to policies that had national or federal impact as well as for the home institution eg end of life care (all), organ donation (US), compassionate therapy (UK), gender identity disorder (Aus). Conclusions: Paediatric CESs in children's hospitals in the US, UK and Australia adhere to adult benchmarks for providing clinical ethics support and also set standards. Despite similar activity profiles, financial and administrative support for CESs and formal funded academic links appears to be greater in the US and Australia than in the UK. Active participation of families in case discussions should be addressed by both Australian and UK CESs if ethical support is to be provided fairly to all involved.